Pengembangan Media Papercraft Pada Mata Pelajaran Bahasa Ndonesia Untuk Keterampilan Menulis Siswa Kelas 2 SDN 11 Sitiung - Angrayni, M; Nurni, Martiya; putri, indah kurnia (Jurnal Ilmiah Dikdaya, 2024)
The purpose of this study is to produce papercraft media for Indonesian language subjects for writingskills of grade 2 students of SDN 11 Sitiung that are valid, practical and effective. The development model usedin this development is the ADDIE development model. In the development of ADDIE there are five stages ofprocedures, namely Analysis, Design (planning), Development (development), Implementation(Implementation) and Evaluation (evaluation). This research with the type of research used is research anddevelopment (R&D). Research and Development (R&D) is a research method used to develop or validateproducts used in education and learning. The validity of the papercraft media that has been carried out by threevalidators obtained an average value of 78.93% with a very valid category. So papercraft can be said to bevalid for use in the learning process. The practicality of papercraft that has been assessed from the teacherresponse questionnaire obtained a score of 93.75% categorized as very practical and the student responseobtained a percentage of 62.42% categorized as practical. The effectiveness of papercraft that has beenassessed from the results of the student learning test obtained a complete score of 15 people with a percentageof 78.94% categorized as effective.